Design of nano-spintronics beamline at 3-GeV next-generation synchrotron radiation facility, NanoTerasu. Issue 1 (1st December 2022) - Ohtsubo, Yoshiyuki; Ueno, Tetsuro; Iwasawa, Hideaki; Miyawaki, Jun; Horiba, Koji; Inaba, Kento; Agui, Akane; Inami, Nobuhito; Nakatani, Takeshi; Imazono, Takashi; Fujii, Kentaro; Kimura, Hiroaki; et al.
Abstract: A synchrotron radiation beamline in the soft- and tender-X ray energy range of 180-3000 eV with versatile polarization control has been designed for NanoTerasu, the 3-GeV next-generation synchrotron radiation facility at Tohoku, Japan. A series of four APPLE-II type undulators is adopted as a photon source to realize the required beam properties with high-speed polarization switching. The beamline optics is designed for a highly efficient and precise use of x-ray magnetic circular/linear dichroism (XMCD/XMLD) technique balancing high photon flux and energy resolution. The simulated performance of the segmented undulator together with the monochromator optics achieved the sufficiently high flux and energy resolution ( E/ΔE ) in whole target energy range. Two endstations with the different re-focus optics, one for marginal spot size with high flux and the other for ultimate focus down to ∼10 nm are also designed. The simulated performance of the beamline encourages the future researches of high-throughput and nm-focused spintronic measurements.